2021
DOI: 10.3390/ma14092448
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Structural Factors for the Electrochemical Performance of Graphene/Carbon Nanotube/Melamine Powders towards the Catalytic Activity of Oxygen Reduction Reaction

Abstract: In this paper, we show the carbonization of binary composites consisting of graphene nanoplatelets and melamine (GNP/MM), multi-walled carbon nanotubes and melamine (CNT/MM) and trinary composites containing GNP, CNT, and MM. Additionally, the manuscript presents results on the influence of structural factors for the electrochemical performance of carbon composites on their catalytic activity. This study contributes to the wide search and design of novel hybrid carbon composites for electrochemical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…The use of carbon nanotubes (CNT) is still limited due to difficulties associated with the dispersion of these nanomaterials and their weak interaction with cementitious matrix. This is because CNT, unlike other spherical particles and carbon fibers, are characterized by small nanometric diameters, high aspect ratio (>1000), and, therefore, a large surface area [1,2]. The effect of CNT on the mechanical performance of cement-based materials is not a consensus in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The use of carbon nanotubes (CNT) is still limited due to difficulties associated with the dispersion of these nanomaterials and their weak interaction with cementitious matrix. This is because CNT, unlike other spherical particles and carbon fibers, are characterized by small nanometric diameters, high aspect ratio (>1000), and, therefore, a large surface area [1,2]. The effect of CNT on the mechanical performance of cement-based materials is not a consensus in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a two-dimensional carbon material that was first successfully prepared by Novoselov and Geim in 2004 [ 13 ]. Since graphene has high conductivity, carrier mobility, and specific surface area, it has been widely used in fuel cells [ 14 ], solar cells [ 15 ], oxygen evolution reactions [ 16 ], oxygen reduction reaction [ 17 , 18 , 19 ], and SCs [ 20 ]. However, in practical applications, graphene may be agglomerated and stacked, and therefore, the charge accumulation of the electric double layer could be limited [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a combination of LDH with conductive support can reduce the agglomeration of LDH and promote its electrocatalytic activity [27]. Several studies found a relationship between the material particle size and its activity in a certain electrochemical application [28][29][30]. In this context, it is important to decrease the composite particle size for better electrochemical performance [31].…”
Section: Introductionmentioning
confidence: 99%